The Connection Between Students Mental Capacity and Learning Outcome in Secondary Schools (Universitas Pendidikan Indonesia Kampus Cibiru, 2024)
The aim of this study is to examine the connection between students’ mental capacity and learning outcome in secondary schools. Learning outcome is the result of education in which student, teacher or institution were able to derived their educational aims and objectives. The participant for this study will comprises of 190 teachers in secondary schools in education district 1. The research design for this study was correlational research design type. Data Were Collected Using The